Chemical constituents and biological activities of the genus Subergorgia - Amir, Faheem; Yam, Wan Sinn; Koay, Yen Chin (Pharmacognosy Reviews, 2012)
The genus Subergorgia (coelenterata, Gorgonacea, Subergorgiidae) is distributed in the Indo-pacific region. Previous investigations on the various species of the genus have revealed the presence of a number of new compounds including alkaloids, sesquiterpenes, diterpenes, and steroids. Certain biological activities particularly cytotoxic activity have been observed for the isolated constituents and compositions derived from the coral. This review covers the secondary metabolites reported from the genus Subergorgia and their biological properties.
Keywords: Alkaloids; cytotoxic activity; steroids; Subergorgia; terpenes